INVESTIGATING THE FACTORS INFLUENCING THE PURCHASING DECISION OF CUSTOMER - Ahmed Khooharo, Tanveer; Tunio, Shahnawaz; khatyan, Azad; Khan Bhutto, Suhrab (The journal of contemporary issues in business and government, 2022)
Theobjective of our research is to study the impact of the factors which affects the purchasing decision of the customers especially in automobiles.Survey using simple random sampling was done at Lahore to customers whose age is round about 18-65 years old. 200 respondents had filled the questionnaires at the sampling location out of which response rate was 92% and 85% of data were reliable. The strength of the relationship between the variables and their normality assumption was met in the correlation analysis.The conclusion derived from this researchwill provide a platform to automobile makers of Pakistan; so that they will understandthe consumerbehavior in Lahore and how it affects the purchasing decision of a customer.